Characterization of granular biopesticide prototypes based on Metarhizium anisopliae for the control ofAncognatha scarabaeoides (Coleoptera: Melolonthidae) - MARIÑO, PAULA; VILLAMIZAR, LAURA; ESPINEV, CARLOS; COTES, ALBA MARINA (Revista Colombiana de Entomología, 2004)
The species Ancognatha scarabaeoides is a coleopteran whose rhizophagous larvae can cause damage in bean, maize, onion, and potato crops, among others. lt causes losses between 1 O and 80% of the total crop. Cultural methods and especially chemical methods with highly toxic insecticides are used for its control. Considering the high economic and environmental costs caused by the use of these products, a promising altemative is the use of biological insecticides based on entomopathogenic fungi like Metarhizium anisopliae. Giving that in previous research at Corpoica, a strain of this fungus (Mt 020) was selected, due to its biocontrol activity of 76,6% against A. scarabaeoides three granular biopesticide prototypes were developed for soil application. Therefore the objective of this work was to determine their physical and microbiological characteristics, and biocontrol activity. For this purpose, the strain was mass produced and three different granulars (GR 1, GR2, and GR3) that varied in components and concentrations were produced. For each granular the particle síze. voluminosity, porosity, fluidity, humidity and pH were determined; as well as the concentration in conídla.g’ and the viability expressed as UFC.g·•. The prototypes and the active source were stored at three temperatures (8, 18 and 28ºC) and the viability of the fungus was evaluated monthly. The biocontrol activity was measured in bioassays carried out in the screen house. According to the results obtained, the granular GRl was selected because of its appropriate physical characteristics, which were equal or inferior to the optimat limits established for each of them. lt had 0,31% fine powder, which means that the granule is not fragile; 3,44 ml.g’ of voluminosity establishing that it will not have manipulation problems; 18% porosity, this small percentage indicates that the granule can resist manipulation without fracturing; it was also established that the product flows easily (angle of repose 27,2°), and so it will not present problems in the filling and packing of large quantities. It had 9, 7% humidity, which guarantees the reduction of metabolic processes, and pH of 5,5. In addition, the maximum loss of viability at the three temperatures presented over the six months of storage was 20, 7%, and it produced promising and stable levels of pest mortality of up to 43%.